15 The creation of the oxford-brazil EBM alliance. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - Fontes, Luis; Riera, Rachel; Vieira, Regis; Pacheco, Rafael; Martimbianco, Ana Luiza; Pachito, Daniela; Miranda, Enderson; Nunan, David
Abstract : Objectives: To describe the experience of building a teaching partnership between the Oxford CEBM and leading Brazilian Medical Schools, thus aiming to increase the effectiveness and quality of EBM teaching in Brazil. Brazil is the 5th largest country in the world, with a population of approximately 210 million people. There are 336 active medical schools in Brazil, which graduate an average of 34, 000 medical professionals each year. Of these schools, less than 20% have in their curricula a formal Evidence-Based Medicine (EBM) discipline. The lack of formal EBM integration into medical school curricula is not exclusively a national challenge for Brazil. Data from the USA and UK suggests that only 60% of curricula include formal EBM content. Despite the recognition of the importance of EBM education and its influence on medical training around the world, challenges remain in integrating EBM education into the medical curriculum, facilitating communication between practitioners, increasing the capacity for EBM's meaningful use in clinical practice, and ensuring medical professionals have the knowledge and skills to support evidence-based practice. Concerned about these issues, two Oxford post-graduate students of Evidence-Based Health Care and a Senior Research Fellow of the Oxford Centre for Evidence-Based Medicine (CEBM) proposed the creation of a partnership between Oxford's CEBM and the EBM Departments of leading Brazilian medical schools. This partnership, named the 'Oxford-Brazil EBM Alliance, ' aims to provide Evidence-Based Medicine and curriculum development training to medical educators (formal professors or tutors) in Brazil, thus fostering sustainability and replicability of effective teaching and learning throughout medical schools in Brazil. Objective: To describe the experience of building a teaching partnership between the Oxford CEBM and leading Brazilian Medical Schools, thus aiming to increase the effectiveness and quality of EBM teaching in Brazil. Method: Descriptive Case Study. Results: Two prominent Brazilian medical schools already joined the Oxford-Brazil EBM Alliance: Escola Paulista de Medicina at Universidade Federal de São Paulo (EPM-UNIFESP) and Faculdade de Medicina de Petrópolis (FMP-FASE). Training will be delivered via 3-day workshops, starting in June 2019, which will be facilitated by faculty from Oxford and Brazil. Other activities may emerge afterwards as instigated by local institutions. This project is underpinned in a concept of developing a 'Center of Excellence in EBM Teaching and Training', which intends to set the standard for EBM teaching in Brazil and throughout South America. It is our overarching aim that over time Brazil will have qualified faculty members to teach EBM in all its Medical Teaching Institutions. To our knowledge, a similar partnership does not exist in our region. In a second phase, we intend to extend this project to other countries in South America, offering further opportunities for international collaboration. Method: Descriptive Case Study. Results: Two prominent Brazilian medical schools already joined the Oxford-Brazil EBM Alliance: Escola Paulista de Medicina at Universidade Federal de São Paulo (EPM-UNIFESP) and Faculdade de Medicina de Petrópolis (FMP-FASE). Training will be delivered via 3-day workshops, starting in June 2019, which will be facilitated by faculty from Oxford and Brazil. Other activities may emerge afterwards as instigated by local institutions. This project is underpinned in a concept of developing a ' Center of Excellence in EBM Teaching and Training', which intends to set the standard for EBM teaching in Brazil and throughout South America. It is our overarching aim that over time Brazil will have qualified faculty members to teach EBM in all its Medical Teaching Institutions. To our knowledge, a similar partnership does not exist in our region. In a second phase, we intend to extend this project to other countries in South America, offering further opportunities for international collaboration. Conclusions: The Oxford - Brazil EBM Alliance is a promising partnership that can bring Evidence-Based Medicine training to thousands of medical professors and interdisciplinary health care teams throughout Brazil and its neighboring countries. The proposed 'teach the teacher' approach can facilitate EBM teaching and learning, foster future leaders, and ultimately benefit patients and healthcare systems throughout Brazil.